Pulsed Dye Laser Does Not Seem as Effective as Red Light in Basal Cell Carcinoma Mal-Pdt: A Small Pilot Study - M. Fernández-Guarino; A. Harto; P. Jaén (Journal of Skin Cancer)
Multiple light sources can be used for photodynamic therapy (PDT) with good results, but there are few comparative studies. This study compares the efficacy of treatment of basal cell carcinoma with PDT and two light sources, the non-coherent red light and pulsed dye laser 595 nm. In this small pilot study red light is more effective, but many more studies are needed to draw definitive conclusions.